Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Раздел:

Номер №78

Преобразуйте в дробь выражение:
а)
$\frac{1}{ab} + \frac{1}{ac} + \frac{1}{bc}$
;
б)
$\frac{ab - b}{a} - \frac{ab - a}{b} - \frac{a^2 - b^2}{ab}$
;
в)
$\frac{b - a}{ab} + \frac{c - b}{bc} - \frac{c - a}{ac}$
;
г)
$\frac{3ab + 2b^2}{ab} - \frac{a + 2b}{a} + \frac{a - 2b}{b}$
.

Решение а

$\frac{1}{ab} + \frac{1}{ac} + \frac{1}{bc} = \frac{c + b + a}{abc}$

Решение б

$\frac{ab - b}{a} - \frac{ab - a}{b} - \frac{a^2 - b^2}{ab} = \frac{b(ab - b) - a(ab - a) - (a^2 - b^2)}{ab} = \frac{ab^2 - b^2 - a^2b + a^2 - a^2 + b^2}{ab} = \frac{ab^2 - a^2b}{ab} = \frac{ab(b - a)}{ab} = b - a$

Решение в

$\frac{b - a}{ab} + \frac{c - b}{bc} - \frac{c - a}{ac} = \frac{c(b - a) + a(c - b) - b(c - a)}{abc} = \frac{bc - ac + ac - ab - bc + ab}{abc} = \frac{0}{abc} = 0$

Решение г

$\frac{3ab + 2b^2}{ab} - \frac{a + 2b}{a} + \frac{a - 2b}{b} = \frac{3ab + 2b^2 - b(a + 2b) + a(a - 2b)}{ab} = \frac{3ab + 2b^2 - ab + 2b^2 + a^2 - 2ab}{ab} = \frac{4b^2 + a^2}{ab}$